Lithuanian Non-Life Insurance Market and Outlook of its Future Development - Baranauskas, Mindaugas; Kindurys, Vytautas (Ekonomika, 2003)
The main purpose of this article is to evaluate current state of Lithuanian non-life insurance market and estimate its future development trends.The article consist of four main parts: analysis of volume of Lithuanian market of non-life insurance and its state relative to the other European non-life insurance markets; analysis of competition and concentration levels of Lithuanian non-life insurers; analysis of non-life insurance consumers; outlook of future development of Lithuanian non-life insurance market.Authors researched all available statistical data concerning Lithuanian non-life insurance market and corresponding data of Eastern, Central, and Western Europe insurance markets. This analysis revealed that Lithuanian non-life insurance market is in its early development stage. All structures and insurance products arc in place, but insurance volumes arc very low relative to European level. The supply side of Lithuanian non-life: insurance market is characterized by very high market concentration. Despite high number of insurance companies market is dominated by few biggest companies. Same situation is typical for all post-communistic countries. The consumers’ side of Lithuanian non-life insurance market is characterized by low purchasing power of inhabitants, and luck of perception of essence and benefits of insurance. But all indicators suggest rapid development of the Lithuanian non-life insurance market in the nearest future. This development is closely related with growth of whole Economy of Lithuania. In light of approaching EU membership rapid grow of Lithuanian non-life insurance market as well as whole economy is very likely.